P181 Detection of anti-neutrophil cytoplasmic antibodies: a single-centre evaluation of the value of indirect immunofluorescence versus antigen-specific immunoassays. (20th April 2020) - Cleaton, Natasha; Adizie, Tochukwu; Barkham, Nick
Abstract: Background: Anti-neutrophil cytoplasmic antibodies (ANCAs) are valuable laboratory markers used for the diagnosis of medium and small-vessel vasculitis, including granulomatosis with polyangiitis (GPA), eosinophilic granulomatosis with polyangiitis (EGPA) and microscopic polyangiitis (MPA). According to the 1999 international consensus, indirect immunofluorescence (IIF) should be used to screen for ANCAs; samples containing ANCAs should then be tested by immunoassays for proteinase 3 (PR3)-ANCAs and myeloperoxidase (MPO)-ANCAs. As dependable immunoassays for PR3ANCAs and MPO-ANCAs have become broadly available, there is increasing agreement that high-quality immunoassays are the preferred screening method for the diagnosis of ANCA-associated vasculitis (AAV). This single centre study was performed to evaluate the accuracy of MPO and PR3 immunoassays in comparison to IIF in the diagnosis of AAV. Methods: We retrospectively reviewed the clinical information of patients that underwent ANCA testing between 1/6/19-30/6/19, via our electronic web portal. Data collected included patients' demographics, ANCA /MPO/PR3 result, and diagnosis as established by their treating physician. A total of 403 ANCA requests were submitted to the Immunology Department at the Royal Wolverhampton NHS Trust. We excluded 55 patients with insufficient information. Due to multiple ANCA tests in a single patient we included only the first test request. Therefore, the study population includes 345 patients. IIF at our centre is performed for all ANCA requests using a commercially available ASP1200 automated dilutor to process the IIF slides with Werfen (Inova) ANCA slides. For the detection of antibodies against MPO and PR3 a commercially available immuno-assay Phadia-250 ImmunoCAP analyser is used in patients with positive IIF. Diagnostic performance was assessed using sensitivity and specificity. Results: The proportion of ANCA negative patients by IIF (177 patients, 51.3%) was almost identical to that of the ANCA positive group (168 patients, 48.7%). Only 13 patients (3.8%) received a diagnosis of AAV. Of the ANCA positive patients 12 (7.1%) had an AAV. 6 of the 13 patients with vasculitis had a supportive tissue biopsy. One ANCA negative patient and one ANCA positive MPO/PR3 negative patient had a diagnosis of vasculitis, previously diagnosed and now on steroid treatment; both were ANCA and MPO positive at diagnosis. 15 patients were MPO or PR3 positive, 11/15 had a diagnosis of vasculitis (73%). Our data found IIF has a sensitivity of 91.67%, specificity 53.01% for detection of AAV. In comparison immunoassay was found to have a sensitivity of 91.67% and specificity of 97.44%. Conclusion: ANCAs are helpful in the diagnosis of AAV, but their use as a diagnostic biomarker should be undertaken in the appropriate clinical context. Immunoassay has a superior diagnostic performance at our centre. Our data suggests screening for ANCA with IIF is not of added value when using high-quality antigen-specific immunoassays. Disclosures: N. Cleaton None. T. Adizie None. N. Barkham None.